Advertising as distortion of learning in markets with network externalities - Kjell Arne Brekke; Mari Rege (University of Oslo, Department of Economics, 2006)
We present a theory of how advertising can break a lock-in by distorting beliefs about market shares in markets with network externalities. On the background of the availability heuristic we assume that people learn about market shares by observing product adoption of others, but are not able to fully distinguish between observations of real people and …ctitious characters in advertisements. We look at a game between an incumbent and an entrant producing close substitutes. Our analysis shows that if the entrant's product is of su ciently high quality, then the entrant will use advertising in order to break the lock-in and the incumbent will not advertise at all. However, if the quality dierential between the two products is small, then the incumbent may advertise and make it unpro…table for the entrant to break the lock-in.
Keywords: D21; L10; M37; 330; Advertising; availability heuristic; herding behavior; information; lock-in; Konsumentenverhalten; Wettbewerb; Produktqualität; Konsumentenverhalten; Network Externalities; Theorie